Health utilities for controlled and uncontrolled chronic hand eczema in healthcare employees. (22nd August 2017) - Küster, Denise; Haufe, Eva; Rethberg, Constanze; Bauer, Andrea; Seidler, Andreas; Schmitt, Jochen
Summary: Background: Health utilities provide a universally applicable method for measuring the relative preferences or values of specific health states. Health economic studies use health utilities to estimate disease burden and the cost‐effectiveness of interventions. Chronic hand eczema (CHE) affects many individuals and adversely affects work productivity. Health utilities for CHE from the perspective of healthcare professionals are lacking. Objectives: To assess health utilities for CHE from the perspectives of employees in the healthcare sector and affected patients. Methods: A cross‐sectional study with volunteers from the healthcare sector (n = 126) and patients (n = 32) was conducted to establish health utilities (ranging from 1 = perfect health to 0 = death) for mild and severe CHE. Results: The median health utilities of the healthy volunteers derived with the time trade‐off method were 0.97 (mean: 0.92) for mild CHE and 0.77 (mean: 0.75) for severe CHE. The median health utilities for mild and severe CHE from the perspective of affected patients were 0.98 (mean: 0.91) and 0.82 (mean: 0.77), respectively. Differences in health utilities between the two study groups were not significant. Conclusion: CHE constitutes a considerable burden from the perspective of healthcare employees. Effective control of CHE constitutes an important public health goal.